2002
DOI: 10.1530/eje.0.1470535
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone protects against radiotherapy-induced cell death

Abstract: Background: In vivo treatment with growth hormone reduces radiation-associated mortality. The molecular mechanisms underlying this effect are unknown. It has been described that increased sensitivity to ionising radiation can be due to defects in machinery involved in detection and/or repair of DNA double-strand breaks. Objective: To study the mechanisms involved in growth hormone action on the increased survival in irradiated cells. Materials and methods: CHO-4 cells stably expressing the growth hormone recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Treatment of irradiated or aged mice with rhGH significantly reduced bone marrow hypocellularity and restored haematopoiesis [60] while a fourth study has demonstrated decreased severity of radiotherapy-induced dermatitis in rats consequent of GH administration [61]. GH administration also protects Chinese hamster ovary cells stably expressing the GHR from radiation and bleomycin-induced cell death [62]. The beneficial aspects of hGH administration in these settings is apparent; however with recent evidence implicating hGH in oncogenesis, perhaps caution should taken when translating these findings into a clinical setting.…”
Section: Hgh and Radiotherapymentioning
confidence: 99%
“…Treatment of irradiated or aged mice with rhGH significantly reduced bone marrow hypocellularity and restored haematopoiesis [60] while a fourth study has demonstrated decreased severity of radiotherapy-induced dermatitis in rats consequent of GH administration [61]. GH administration also protects Chinese hamster ovary cells stably expressing the GHR from radiation and bleomycin-induced cell death [62]. The beneficial aspects of hGH administration in these settings is apparent; however with recent evidence implicating hGH in oncogenesis, perhaps caution should taken when translating these findings into a clinical setting.…”
Section: Hgh and Radiotherapymentioning
confidence: 99%
“…Due to evidence suggesting a radioprotective role for GH (Gomez-de-Segura et al 1998, Vazquez et al 1999, Mylonas et al 2000, Isla et al 2002, Madrid et al 2002, Raguso et al 2002, Lempereur et al 2003, N M Bougen et al: Autocrine human GH is radioprotective www.endocrinology-journals.org Morante et al 2003, Tekin et al 2006, we investigated whether autocrine hGH enhanced mammary and endometrial cancer cell viability following treatment with IR. Three pairs of stably transfected cell lines (MDA-vec and MDA-hGH, T47D-vec and T47D-hGH and RL95-vec and RL95-hGH cells) were exposed to an initial treatment range of 0-8 Gy IR.…”
Section: Resultsmentioning
confidence: 99%
“…Although we did not observe any effect on the DNA repair capacity using the neutral comet assay, an effect on DNA repair cannot be ruled out. A study by Madrid et al (2002) demonstrated that the radioprotective effect mediated by exogenous GH in CHO-4 cells stably expressing the GHR was associated with an enhanced ability of the cells to repair damaged DNA, indicating that GH may activate pathways involved in DNA repair processes. Further investigation using assays interrogating different DNA repair pathways would determine whether autocrine hGH impacted on the DNA repair capacity of breast and endometrial cancer cell lines.…”
Section: N M Bougen Et Al: Autocrine Human Gh Is Radioprotectivementioning
confidence: 99%
See 1 more Smart Citation
“…IGFBP-3 inhibits estrogen induced proliferation of breast cancer cells as well as promoting apoptosis of cancer cells [76]. HGH repairs DNA damage inflicted on cells by carcinogens and radiation [77]. It increases the activity of "Natural Killer Cells" [78].…”
Section: -Tri-iodothyronine [T3]mentioning
confidence: 99%